Emission analysis of palm stearin biodiesel fuelled diesel engine. Issue 14 (5th December 2020) - Ganesh, R.; Manikandan, K.; Chandran, Jishu
ABSTRACT: This work presents the practicability of using palm stearin oil (PSME) as an alternate on diesel blended fuel to evaluate the emission characteristics. Six blends of fuels namely, neat diesel, biodiesel (palm stearin methyl ester), a blend of diesel–biodiesel (20%, 40%, 60%, and 80%) are prepared and tested in a diesel engine. The experimental results were revealed that the replacement of diesel by PSME has shown a significant reduction of unburned hydrocarbon, Smoke, CO, and NOx emissions.